E-Learning Management System for King Saud University - Zafer F, Alduhaim Norah (2012)
The purpose of this study is to develop an e-learning management system for King Saud University to be as a basis to develop an e-learning management system and to assist the lecturers in managing the learning materials with the students. To develop such system, the general methodology has been used and developed using java programming (JSP) which facilitates good design and services.Questionnaire has been used as a usability technique for purpose of evaluating the system in terms of visibility of system statues and contents, learnability and accessibility, flexibility and efficiency of use, usefulness, and effectiveness and satisfaction. The evaluation reveals that 86.56% of the participants indicated that the prototype effectiveness and satisfaction which is high and agreed altitude.